A Cysteine-Rich Protein Kinase Associates with a Membrane Immune Complex and the Cysteine Residues Are Required for Cell Death. Issue 1 (16th November 2016) - Yadeta, Koste A.; Elmore, James M.; Creer, Athena Y.; Feng, Baomin; Franco, Jessica Y.; Rufian, Jose Sebastian; He, Ping; Phinney, Brett; Coaker, Gitta
Abstract : Arabidopsis CRK28 is synthesized upon immune perception, associates with the FLS2 receptor complex, and silencing multiple related CRKs enhances disease susceptibility. Abstract: Membrane-localized proteins perceive and respond to biotic and abiotic stresses. We performed quantitative proteomics on plasma membrane-enriched samples from Arabidopsis ( Arabidopsis thaliana ) treated with bacterial flagellin. We identified multiple receptor-like protein kinases changing in abundance, including cysteine (Cys)-rich receptor-like kinases (CRKs) that are up-regulated upon the perception of flagellin. CRKs possess extracellular Cys-rich domains and constitute a gene family consisting of 46 members in Arabidopsis. The single transfer DNA insertion lines CRK28 and CRK29, two CRKs induced in response to flagellin perception, did not exhibit robust alterations in immune responses. In contrast, silencing of multiple bacterial flagellin-induced CRKs resulted in enhanced susceptibility to pathogenic Pseudomonas syringae, indicating functional redundancy in this large gene family. Enhanced expression of CRK28 in Arabidopsis increased disease resistance to P. syringae . Expression of CRK28 in Nicotiana benthamiana induced cell death, which required intact extracellular Cys residues and a conserved kinase active site. CRK28-mediated cell death required the common receptor-like protein kinase coreceptor BAK1. CRK28 associated with BAK1 as well as the activated FLAGELLIN-SENSING2 (FLS2) immune receptor complex. CRK28 self-associated as well as associated with the closely related CRK29. These data support a model where Arabidopsis CRKs are synthesized upon pathogen perception, associate with the FLS2 complex, and coordinately act to enhance plant immune responses.